Religion and Dialogue in Indonesia: From the Soeharto Period to the Present - Mujiburrahman, Mujiburrahman (Studia Islamika, 2010)
The fact that Indonesia is a multi-religious country may lead us to question if there have been initiatives among di?erent religions to dialogue, and if so, who have been the main advocates of this dialogue, what were the issues being discussed and what are the results of the dialogue? This paper tries to answer these questions by analyzing the development of religious dialogue from the Soeharto period to the present. The historical overview will hopefully give us some lessons to learn for the future of dialogue in Indonesia and perhaps also in the neighboring countries.DOI:Â 10.15408/sdi.v17i3.455Â